Long shared haplotypes identify the Southern Urals as a primary source for the 10th century Hungarians - Gyuris, Balázs; Vyazov, Leonid; Türk, Attila; Flegontov, Pavel; Szeifert, Bea; Langó, Péter; Mende, Balázs Gusztáv; Csáky, Veronika; Chizhevskiy, Andrey A; Gazimzyanov, Ilgizar R; Khokhlov, Aleksandr A; Kolonskikh, Aleksandr G; et al. (bioRxiv, 2024)
During the Hungarian Conquest in the 10th century CE, the early medieval Magyars, a group of mounted warriors from Eastern Europe, settled in the Carpathian Basin. They likely introduced the Hungarian language to this new settlement area, during an event documented by both written sources and archaeological evidence. Previous archaeogenetic research identified the newcomers as migrants from the Eurasian steppe. However, genome-wide ancient DNA from putative source populations has not been available to test alternative theories of their precise source. We generated genome-wide ancient DNA data for 131 individuals from candidate archaeological contexts in the Circum-Uralic region in present-day Russia. Our results tightly link the Magyars to people of the Early Medieval Karayakupovo archaeological horizon on both the European and Asian sides of the southern Urals. Our analyes show that ancestors of the people of the Karayakupovo archaeological horizon were established in the Southern Urals by the Iron Age and that their descendants persisted locally in the Volga-Kama region until at least the 14th century.